Teachers' awareness and utilization of assessment techniques as predictors of students' achievement in english reading comprehension in Ibadan North local government area (2019)
This study investigated teachers' awareness and utilization of assessment techniques as predictors of students' achievement in English reading comprehension in Ibadan North Local Government. Descriptive research design of correlational type was adopted. Simple random sampling technique was used to select thirty English language, teachers and nine hundred and sixty students from public senior secondary schools in Ibadan North Local Government. The instruments used for data collection were: Questionnaire on English Language Teachers' Awareness of Assessment Techniques in Reading Comprehension (OOELTAARC) (0.77). English Language Teachers' Observation Scale on the Utilization of Assessment Techniques in Reading Comprehension (ELTOSUATRC) (0.75) and Reading Comprehension Achievement Test (RCAT) (0.88). Data collected were analyzed using Descriptive Statistics of Mean. Standard Deviation. Frequency Count and Percentage. Pearson Product Moment Correlation (PPMC) and Multiple Regression Analysis. Findings revealed that there were negative, non significant relationships between English language teachers' awareness of assessment techniques, utilization of assessment techniques and students' achievement in Reading Comprehension. The composite contribution of English language teachers' awareness and utilization of assessment techniques to students' achievement in Reading Comprehension was not significant. The relative contribution of English language teachers' awareness of assessment techniques, utilization of assessment technique to students' achievement in Reading Comprehension was not significant. None of the independent variables significantly predicts students' achievement in Reading Comprehension. Based on the findings, it was recommended that various assessment techniques should be given more prominence in assessing students' achievement in Reading Comprehension.